The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1063/1.3327436
|View full text |Cite
|
Sign up to set email alerts
|

Site of incorporation and solubility for Fe ions in acceptor-doped PZT ceramics

Abstract: Difference between resistance degradation of fixed valence acceptor (Mg) and variable valence acceptor (Mn)doped BaTiO 3 ceramics

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…23 The low symmetry of the Mössbauer signal at the central position in Fe-doped TiO 2 (B) is due to the presence of more oxygen vacancies-Fe dipoles interaction compared to Fe-doped anatase nanorods. 24 The absence of any sextet in fit-derived Mössbauer spectra clearly showed that the ferromagnetic component in the samples is not due to metallic iron and iron oxide. 25 Fig .…”
Section: Resultsmentioning
confidence: 99%
“…23 The low symmetry of the Mössbauer signal at the central position in Fe-doped TiO 2 (B) is due to the presence of more oxygen vacancies-Fe dipoles interaction compared to Fe-doped anatase nanorods. 24 The absence of any sextet in fit-derived Mössbauer spectra clearly showed that the ferromagnetic component in the samples is not due to metallic iron and iron oxide. 25 Fig .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Erdem et al . have reported that, the additional resonance at the g‐factor value of ~2.0 corresponds to the Fe 3+ ‐exchange coupled magnetic secondary phase.…”
Section: Electron Paramagnetic Resonance Studiesmentioning
confidence: 99%
“…However, taking into account Refs. and , in our opinion, small quantities of Fe 2 O 3 at the Fe/PZT interface could be considered as a dopant for PZT material. The acceptor Fe 3+ ions could form alignable and immobile defect dipoles, oxygen vacancies–Fe 3+ ions, which, according to Refs.…”
Section: Resultsmentioning
confidence: 81%
“…The acceptor Fe 3+ ions could form alignable and immobile defect dipoles, oxygen vacancies–Fe 3+ ions, which, according to Refs. and , increase the performance of the PZT material. A key role of the FeO monolayer for ME coupling mechanism at the PZT/Fe interface, similar to those reported in the case of the BaTiO 3 /Fe interface , is expected to be evidenced in the future.…”
Section: Resultsmentioning
confidence: 99%